Development of Multi-Lateral Cooperation for Educational Quality Improvement of Small-Size Schools in Nakhon Pathom Province - Suwan, Sumitr; Thongperm, Athikiat; Ayudhya, Surin Xoomsai Na; Wannagatesiri, Tussatrin; Kruea-in, Nantarat; Maneerat, Sukhon; Nugultham, Kulthida; Fakcharoenphol, Witat (Nurture, 2015)
The research objectives are 1) to develop multi-lateral cooperation between educational institution, schools, communities, temples, local government, public agencies and private sectors to improve the education quality of the small-sized schools, 2) to compare the two development formats of the multi-lateral cooperation and our results show no significant differences between the two formats. The multi-lateral cooperation formed during the processes includes within-school network, near-by-school network, parent and community network, networks with local government, public agencies and private sectors, and network with scholars in the university. These networks should be encouraged and mobilized by further research to produce concrete results.